Identificação de dano em estruturas utilizando uma metodologia que integra a técnica da impedância eletromecânica e ondas de Lamb - Rocha, Lucas Altamirando de Andrade da (2017)
The present work is dedicated to the monitoring of structural health (SHM), that is the development of a procedure that interrogates a structure to detect, locate and identify damages. Today, SHM represents one of the main areas of interest in engineering and it is applied for both maintenance cost reduction and operational safety. In this thesis was performed the fault diagnosis of a panel of material typical of the aeronautical industry, through the integration of two SHM techniques, namely the electromechanical impedance technique and Lamb waves. For the diagnosis, the damage metrics extracted from the impedance signatures of the structure were used together with an algorithm for the location of the damage considering Lamb waves. Temperature compensation techniques were systematically to avoid false diagnoses. A statistical model was developed to establish threshold indices according to a predefined confidence level. Thus, this work presents an evaluation of the sensitivity of the proposed techniques, considering a success rate. To ensure the integration of the two SHM techniques for aeronautical applications, a dedicated hardware was designed so that its architecture allows the cooperative integration of the two SHM techniques used. Finally, the obtained results demonstrate the great potential of the integration of the two techniques proposed in conjunction with the hardware developed the mathematical and computational methodologies.